2021
DOI: 10.3390/su13126649
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Aged Public Buildings and Effect Analysis Prediction of Green Remodeling in South Korea

Abstract: The purpose of this study is to analyze the scope of the expected improvement effect of office buildings and educational research facilities according to green remodeling. Thus, in order to quantitatively grasp the architectural performance of the existing buildings, the building thermal performance, the airtightness, the indoor environment, and the air quality were measured using equipment. The analysis indicated that the envelope performance and the indoor environment were unsatisfactory compared to the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The remodeling period estimation can be calculated as a summation of the normal duration of construction in addition to correction values and risk attributes. Nam et al (2021) analyzed the expected improvement effect of office buildings and educational research facilities, which have undergone green remodeling, quantitatively using measures of indoor environmental qualities. The findings indicated that the performance of these facilities were unsatisfactory, according to the legal requirements and standards.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The remodeling period estimation can be calculated as a summation of the normal duration of construction in addition to correction values and risk attributes. Nam et al (2021) analyzed the expected improvement effect of office buildings and educational research facilities, which have undergone green remodeling, quantitatively using measures of indoor environmental qualities. The findings indicated that the performance of these facilities were unsatisfactory, according to the legal requirements and standards.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A scope may define the zones (indoors, outdoor, levels of work) and remodeling depth (e.g. structural, configurational, equipment and furniture) (Nam et al, 2021) Remodeling built facilities be technical (e.g. environmental, engineering), functional (e.g.…”
Section: Lifecycle Factors Affecting the Successful Delivery Of Remod...mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of air pollutant material reduction is also a social benefit generated by the reduced consumption of electricity and energy. The calculation method is the same as that shown in Equation (3) [22]. The social cost of air pollutants was referred to as the social cost per MWh for nitrogen oxide, sulfur oxide, and dust by air pollutants in the preliminary feasibility report of "Smart Grid Expansion Project (2015)" of KDI.…”
Section: Benefit Of Annual Carbon Emission Reduction (Usd/y) = (Annua...mentioning
confidence: 99%
“…However, this GR is not a measure that can be adopted by all owners of old buildings, because of the high initial construction cost which requires about 10 years (relatively long term) to recover the construction cost [22]. This is particularly true for low-income elderly households who experience a relatively large impact on energy bill burden, indoor environment, and air pollution.…”
Section: Introduction 1background and Purposementioning
confidence: 99%